2019
DOI: 10.1111/gcb.14564
|View full text |Cite
|
Sign up to set email alerts
|

Responses of an endangered brown bear population to climate change based on predictable food resource and shelter alterations

Abstract: The survival of an increasing number of species is threatened by climate change: 20%–30% of plants and animals seem to be at risk of range shift or extinction if global warming reaches levels projected to occur by the end of this century. Plant range shifts may determine whether animal species that rely on plant availability for food and shelter will be affected by new patterns of plant occupancy and availability. Brown bears in temperate forested habitats mostly forage on plants and it may be expected that cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 76 publications
(146 reference statements)
4
51
0
Order By: Relevance
“…Therefore, the achievement of accurate spatial products informing on spatial and temporal variation of key trophic resources is essential for developing realistic conservation strategies at regional scale. Comparing our results with a recent prediction made for the target species in the study area on the basis of forestry occurrence and climatic data (Penteriani et al 2019), we found that using habitat predictors (including habitat maps or remote sensing data) in partitioned models allowed for achieving spatial products with higher spatial precision at regional scale. While the use of remote sensing data reflects more accurately the local area of occupancy (Álvarez-Martínez et al 2018), the use of habitat maps and bedrock layers allows for removing limestone-dominated areas, which could have been overlooked when using only topo-climatic variables.…”
Section: Implications For Conservationsupporting
confidence: 51%
See 1 more Smart Citation
“…Therefore, the achievement of accurate spatial products informing on spatial and temporal variation of key trophic resources is essential for developing realistic conservation strategies at regional scale. Comparing our results with a recent prediction made for the target species in the study area on the basis of forestry occurrence and climatic data (Penteriani et al 2019), we found that using habitat predictors (including habitat maps or remote sensing data) in partitioned models allowed for achieving spatial products with higher spatial precision at regional scale. While the use of remote sensing data reflects more accurately the local area of occupancy (Álvarez-Martínez et al 2018), the use of habitat maps and bedrock layers allows for removing limestone-dominated areas, which could have been overlooked when using only topo-climatic variables.…”
Section: Implications For Conservationsupporting
confidence: 51%
“…These climatic features, together with the uneven topography and the historical land management, have resulted in a highly heterogeneous landscape that host a wide variety of ecosystems, habitats and endemic species. In these mountains, that have been recognized as a hotspot of biodiversity (Worboys et al 2010;García-Llamas et al 2016, bilberry has a regional interest as a trophic resource for endangered species, such as the Cantabrian Capercaille (Blanco-Fontao et al 2009) and the Cantabrian Brown Bear (Rodríguez et al 2007;Penteriani et al 2019). The species mainly occurs in acidic vegetation related to northern exposures and can be found across three habitats: acidic woodlands, Atlantic heathlands and alpine dwarf-shrublands (Table 1 and Annex 1 of the Supplementary material).…”
Section: Study Casementioning
confidence: 99%
“…Acknowledging that global warming could push these refuge areas to higher elevations, the increased accessibility of humans to mountain areas (Godde, Price & Zimmermann, ), partly a consequence of milder winters, needs to be managed in order to guarantee that bears can cope with it. As it is almost impossible however to restrict human access into bear habitat or closer to human settlements (Penteriani et al , ), a separation of humans and bears in time in Greece (i.e. regulating human activities during the night and crepuscular hours) should reduce negative human–bear interactions and increase survival chances.…”
Section: Discussionmentioning
confidence: 99%
“…(Martínez Cano et al ., 2016) and the mountain range has an Atlantic climate, characterized by mild winters and rainy summers (Pato & Obeso, 2012). Forests of oak ( Quercus petraea , Quercus pyrenaica and Quercus robur ), beech ( Fagus sylvatica ), chestnut ( Castanea sativa ) and white birch ( Betula pubescens ) are dominant, alternating with pastures and brushwoods and subalpine scrubs (Penteriani et al ., 2019; Zarzo‐Arias et al ., 2019). The western Cantabrian subpopulation, estimated to hold around 280 bears (2017), inhabits an area of more than 7.000 km 2 with an average human population density of 10.9 inhabitants/km 2 and a road density of more than 0.5 km/km 2 , while the eastern subpopulation, with around 50 bears (2017), occupies around 4.000 km 2 with c .…”
Section: Methodsmentioning
confidence: 99%